Matrix metallopeptidase 9 and outcome prediction in patients with acute coronary syndrome - A. O. Bilchenko; I. R. Vyshnevska; Ya. V. Hilova; M. P. Kopytsia (Zaporozhye State Medical University, 2022)
The aim of this review was to analyse the scientific literature data on matrix metallopeptidase 9 and to analyse the available information on its prognostic value as a marker of negative outcome in the short- and long-term prognosis in patients with acute coronary syndrome. Materials and methods. In our study was used a recursive literature search strategy at PubMed. The following criteria for inclusion in the analysis were defined - a prospective study in patients with acute coronary syndrome that had data on the effect of MMP-9 levels on short-term and/or long-term outcomes, including mortality and major adverse сardiovascular events. Review articles, clinical cases, animal studies, and studies with insignificant statistical data were not included in the analysis. The depth of the initial search was set at 15 years with a search for similar articles in citations. We selected 5 studies for meta-analysis. Meta-Essentials 1.5 was used for the analysis. Odds ratio and 95 % confidence interval were calculated using the Haenszel method. The association between MMP-9 levels and short-term and long-term outcomes (mortality and major adverse CV events) was determined. The statistically significant level was defined as P < 0.05. Results. The analysis showed no significant association between the level of MMP-9 and the outcome (OR = 1.39; 95 % CI = 0.25-7.79; P = 0.595; I2 = 78 %). Conclusions. Matrix metallopeptidase 9 is a promising marker for further investigation of its predictive strength of outcome. Despite the opposite results of single studies and no significant association of MMP-9 with outcome further research on this issue is a promising direction.